A comprehensive comparative study of MOM for adaptive interoperability communications in service oriented architecture - Muhamad Ibrahim, Najhan; Hassan, Mohd Fadzil (2019)
Numerous software platforms have developed to support several application systems with a variety of techniques and solution. The communications between those platforms are required to ensure tasks distributed across different application systems. The collaboration between distinct application systems to grow, in tandem with the growth of SOA in which the resources of each SOA application might be developed and implemented using different standard and specification. Within this context, interoperability communications is significant to consolidate the optimization of these resources. Additionally, identifying the requirements attribute related to interoperability communications are the first step required in the development of interoperability communications. MOM can be considered as a tool for enabling the communications between distributed applications where the transaction or event notifications are delivered between distributed applications through the message. MOM provides a program-to- program connection by message passing. Most of the MOM environments are implemented using queued message store-and-forward capability, which is Message Queuing Middleware (MQM). In addition, an adaptive interoperability communications can be defined as the computer system that enables self- coordination to distribute computing resources and an adaptive to the new environment while hiding fundamental complexity from the operators and users. The intelligent system has the capability of self-management to overcome the rapidly growing complexity in computing systems. The system makes decisions on its own by using the rules that have been identified. Intelligent system also provides an adaptive and dynamic environment for the process of communication. The framework of an intelligent system, fundamentally consists of intelligent elements. Each element performs a fixed function and interacting with other elements in a very dynamic environment.